194 Efficacy of Primary Microvascular Decompression vs Salvage Microvascular Decompression for Trigeminal Neuralgia. (1st August 2016) - Goodwin, C. Rory; Theodros, Debebe; Abu-Bonsrah, Nancy A.; Bender, Matt; Zhou, Xin; De la Garza-Ramos, Rafael; Mathios, Dimitrios; Garzon-Muvdi, Tomas; Blitz, Ari M; Olivi, Alessandro; Carson, Benjamin S.; Bettegowda, Chetan
Abstract: INTRODUCTION: Trigeminal neuralgia (TN) is a pain disorder characterized by paroxysmal lancinating pain along the distribution of the trigeminal nerve. Mounting clinical evidence supports the neurovascular compression (NVC) theory, suggesting vascular compression results in the manifestation of debilitating pain. Microvascular decompression (MVD) is the only known surgical intervention that directly addresses this proposed etiology. METHODS: A retrospective review of patient records at the Johns Hopkins Hospital from 1998 to 2015 revealed 942 patients with TN and 500 patients who underwent MVD. A total of 306 patients who underwent MVD initially and 175 patients who underwent salvage MVD were included for analysis. Demographics, preoperative interventions, pain outcomes, pre- and postoperative sensory outcomes, and complications were collected. RESULTS: Patients who underwent salvage MVD were older (55.22 years vs 49.98 years, P < .001), and experienced symptoms longer (7.22 years vs 4.45 years, P <.001). Patients who underwent MVD initially experienced improved pain relief and no pain relief rates compared with those who had salvage MVD (95.8% and 4.2% vs 90.3% and 9.7%, respectively, P = .004). Patients who underwent MVD initially had significantly lower rates of facial numbness in the pre- and postoperative period compared with salvage MVD patients ( P < .001). The number of complications between both groups was similar ( P = .457). CONCLUSION: Our results suggest that patients who underwent procedures prior to MVD experienced less pain relief and a higher incidence of facial numbness despite similar rates of complications in comparison with patients who underwent MVD as their first surgical intervention.